Preparation method of biomass hard carbon negative electrode material with low specific surface area

By preparing biomass hard carbon anode material with low specific surface area and using asphalt to fill the pore structure of the surface of the carbon material, the problem of high irreversible capacity caused by the large specific surface area of ​​the hard carbon anode material is solved, the Coulomb efficiency and specific capacity are improved, and the The energy density of sodium ion batteries.

CN119191265APending Publication Date: 2024-12-27JINGDONG TECHNOLOGY (SHENZHEN) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411331237.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The specific surface area of ​​the hard carbon negative electrode material is large, resulting in high irreversible capacity for the first charge and discharge of the electrode and low Coulomb efficiency, which affects the energy density of the sodium ion battery.

Method used

The preparation method of low specific surface area biomass hard carbon negative electrode material is adopted, and the large surface covering the surface of the carbon material is filled with asphalt by pretreatment, low-temperature carbonization, crushing, pickling, fine grinding, asphalt fusion, oxidation modification and high-temperature carbonization processes. Pores or mesopores, forming a hard carbon negative electrode material with a low specific surface area.

Benefits of technology

The irreversible capacity of the electrode for the first charge and discharge is reduced, the Coulomb efficiency and specific capacity are improved, and the performance consistency and rate performance of hard carbon materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191265A_ABST
    Figure CN119191265A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biomass hard carbon negative electrode material with low specific surface area, which comprises the following steps: S1, pretreating a biomass raw material to obtain a carbon precursor; s2, carbonizing the carbon precursor at low temperature; s3, crushing and processing low-temperature carbides; s4, preparing a pickling solution for pickling; s5, fine grinding after acid pickling; s6, fusion: fusing a product obtained after fine grinding with asphalt to form a carbon precursor; s7, performing air oxidation modification to obtain an oxidized carbon precursor; s8, carrying out high-temperature carbonization treatment on the oxidized carbon precursor; S9, scattering and dissociating; s10, screening is carried out; and preparing the sodium-ion battery hard carbon negative electrode material. The surface of the biomass carbon material is coated with asphalt, macropores or mesopores on the surface are filled and coated with the asphalt, and then a hard carbon structure is formed through air oxidation and high-temperature carbonization, so that the specific surface area and the first charge-discharge irreversible capacity of the material are reduced, and the coulombic efficiency and the specific capacity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method, in particular to a preparation method of a biomass hard carbon negative electrode material with a low specific surface area. Background Art

[0002] Sodium-ion battery is a new type of secondary battery with the advantages of abundant raw material resources, low production cost, excellent rate charge and discharge performance, good safety performance, and wide operating temperature range. It is expected to replace lead-acid batteries as a supporting power source for two-wheeled vehicles and low-speed vehicles, and will be widely used in energy storage fields such as wind and solar power generation and grid peak regulation. Sodium-ion batteries usually use soft carbon or hard carbon with an amorphous structure as the negative electrode active material. Among them, hard carbon materials have a large interlayer spacing and irregular structure, which are suitable for sodium ion insertion and extraction, have low sodium storage potential and high sodium storage specific capacity, and the precursor is widely available and low in price. It is known as the most promising sodium storage negative electrode material.

[0003] As the negative electrode material of sodium-ion batteries, hard carbon has been proposed to have a variety of sodium storage mechanisms. Based on the current research status in recent years, there are three main types of sodium storage behaviors of hard carbon: (1) adsorption of surface heteroatoms, defect sites and functional groups; (2) intercalation between graphite carbon layers; (3) filling of micropores. The internal graphite crystallites of hard carbon materials are small in size and arranged in a disordered manner, which in turn form many microporous structures. In particular, the surface micropores are well developed and there are many open pores, resulting in a large specific surface area of ​​the material. At the same time, due to the low sodium storage capacity of the open pores, the electrode has a high first charge and discharge irreversible capacity and low coulombic efficiency, which affects the energy density of the battery. Based on this, the defect of high first irreversible capacity of hard carbon negative electrode materials needs to be solved urgently. Summary of the invention

[0004] In order to solve the shortcomings of the above-mentioned technology, the present invention provides a method for preparing a biomass hard carbon negative electrode material with a low specific surface area, comprising the following preparation steps: S1. Pretreatment: pretreating the biomass raw material to obtain a carbon precursor; S2. Low-temperature carbonization: heating the carbon precursor at a temperature of 300-600°C to obtain a low-temperature carbide; S3, crushing: cooling the low-temperature carbide to room temperature and then crushing it; S4, pickling process: prepare pickling liquid and pickle the crushed low-temperature carbide; S5, fine grinding: finely grind the pickled material to the required particle size; S6. Fusion: Fusion of the finely ground product with asphalt, where the asphalt fills and coats the macropores or mesopores on the surface of the carbon material to form a carbon precursor; S7, oxidation modification: blowing the carbon precursor with hot air at 150-350° C. for 1-3 hours to obtain an oxidized carbon precursor; S8, high temperature carbonization: subjecting the oxidized carbon precursor to high temperature carbonization treatment to form a hard carbon negative electrode material for a sodium ion battery; Preferably, the preparation method further comprises the following steps: S9. Break up: After high-temperature carbonization, cool the material to below 200°C and take it out. Use mechanical means to break up the agglomerated or compacted material into powder; S10, sieving: the powdered material after being dispersed is passed through a 200-500 mesh ultrasonic vibration screen to obtain the final product of the hard carbon negative electrode material for sodium ion batteries. The material on the screen is returned to the dispersing step for further processing.

[0005] Preferably, the biomass used is any one or more of nut shells such as almond shells, coconut shells, walnut shells, sisal leaves, crop straw, etc.; The asphalt used is medium-temperature or high-temperature asphalt, which is crushed into micron-sized powder.

[0006] Preferably, the pretreatment method includes cleaning, drying or crushing.

[0007] Preferably, in S2, the specific operations of the low-temperature carbonization treatment include: putting the carbon precursor into a vacuum heating furnace or an inert gas heating furnace for heating and carbonization; When a vacuum heating furnace is used, the furnace is evacuated, the vacuum degree is maintained at 0.04~0.08MPa, the heating rate is 3~10℃ / min, the temperature is heated to 300~600℃, and the carbonization time is maintained at this temperature for 2~4h; When heating is performed in an inert gas heating furnace, the heating chamber is first evacuated and then an inert gas is injected. The inert gas can be nitrogen or argon, and the temperature is also heated to 300~600℃.

[0008] Preferably, in S3, the pulverizing process specifically includes: taking out the low-temperature carbide from the vacuum heating furnace or the inert gas heating furnace and cooling it to room temperature, first pulverizing it with a double-roll mill, and then sieving it with a 10-50 mesh screen, and returning the screened material to the double-roll mill for further pulverization.

[0009] Preferably, the pickling solution is composed of the following substances in percentage by mass: 1% to 10% sulfuric acid, 0.1% to 1% hydrofluoric acid, and 1% to 2% hydrochloric acid. After pickling, water washing is performed to wash out the acidic substances, and the filter cake obtained by filtration is then dried.

[0010] Preferably, in S6, the fusion treatment is carried out in a fusion machine, the acid-washed product is fully mixed with asphalt in a mass ratio of 100: (1-15) and then put into the fusion machine for fusion coating to form a carbon precursor.

[0011] Preferably, in S8, the oxidized carbon precursor is placed in a high-temperature carbonization furnace, and an inert gas is introduced. The air in the furnace is driven out by controlling the flow rate of the inert gas, and the inert gas is kept flowing. The temperature is increased from room temperature at a rate of 1 to 10°C / min to a specified carbonization temperature of 1100 to 1500°C. Carbonization is maintained at this temperature for 4 to 16 hours to form a hard carbon negative electrode material for a sodium ion battery.

[0012] The present invention discloses a method for preparing a biomass hard carbon negative electrode material with a low specific surface area, wherein asphalt is fully mixed with a biomass carbon material and then fused, so that the macropores or mesopores on the surface of the biomass carbon material are filled and coated with asphalt, and then a hard carbon negative electrode material with a low specific surface area is formed through subsequent oxidation modification and high-temperature carbonization treatment, so as to achieve the purpose of reducing the irreversible capacity of the first charge and discharge of the electrode and improving the coulomb efficiency and specific capacity. The present invention performs oxidation modification on the asphalt, and uses the oxygen-containing functional groups introduced during the oxidation process to produce a cross-linking effect with the asphalt molecules, inhibits the molten state fluidity during the carbonization process, and forms an amorphous carbon structure. In addition, the small gas molecules released during the heating process produce randomly stacked curved carbon layers inside the amorphous carbon, thereby producing tight pores, which plays a dual regulating role. These wrapped asphalts can also form a precursor of a hard carbon structure through an oxidation process (the present invention specifically adopts air pre-oxidation means), and then a hard carbon negative electrode material with a low specific surface area can be obtained through a subsequent high-temperature carbonization process. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a principle process flow chart of the present invention. DETAILED DESCRIPTION

[0014] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0015] The present invention discloses a method for preparing a biomass hard carbon negative electrode material with a low specific surface area. The central idea is to fully mix asphalt with the biomass carbon material and then fuse them. The asphalt plays a role in filling and coating the macropores or mesopores on the surface of the carbon material. After oxidation and high-temperature carbonization, the biomass-based hard carbon negative electrode material is generated, and the specific surface area of ​​the material is reduced, the initial coulomb efficiency and the sodium storage capacity are improved. The specific preparation process is as follows Figure 1 As shown, the following processes are included: S1. Pretreatment: pretreating the biomass raw material to obtain a carbon precursor; The pretreatment methods include cleaning, drying or crushing, and the biomass raw materials used are: nut shells such as almond shells, coconut shells, walnut shells, as well as one or more of sisal leaves, crop straw, etc.

[0016] S2. Low-temperature carbonization: heating the carbon precursor at a temperature of 300-600°C to obtain a low-temperature carbide; The porosity and specific surface area of ​​the carbon precursor are increased by low-temperature carbonization treatment. The specific operations are as follows: when using a vacuum heating furnace, the furnace is evacuated, the vacuum degree is maintained at 0.04~0.08MPa, the heating rate is 3~10℃ / min, the temperature is heated to 300~600℃, and the carbonization time is maintained at this temperature for 2~4h. If heating is performed in an inert gas heating furnace, the heating furnace is first evacuated and then an inert gas is injected. The inert gas can be nitrogen or argon, and the temperature is also heated to 300~600℃.

[0017] S3, crushing process: after cooling the low-temperature carbide to room temperature, crush it; Specifically, the low-temperature carbide is taken out from the vacuum heating furnace or the inert gas heating furnace, cooled to room temperature, first crushed by a double-roll mill, and then sieved with a 10-50 mesh screen, and the screened material is returned to the double-roll mill for re-crushing.

[0018] S4, pickling process: prepare pickling liquid and pickle the crushed low-temperature carbide; The pickling liquid is prepared from sulfuric acid, hydrofluoric acid and hydrochloric acid according to certain mass percentages, wherein sulfuric acid is 1% to 10%, hydrofluoric acid is 0.1% to 1%, and hydrochloric acid is 1% to 2%. The low temperature carbide is pickled with the above acidic liquid to remove the ash in the low temperature carbide, and after pickling, it is filtered and washed with water, and the obtained filter cake is then dried.

[0019] S5, fine grinding: Use a mechanical mill or air flow mill with a grading device to finely grind the material after S4 pickling to obtain material with a particle size that meets the requirements.

[0020] S6, fusion: the finely ground material is fully mixed with asphalt, and then put into a fusion machine for fusion, and the asphalt fills and coats the macropores or mesopores on the surface of the carbon material to form a carbon precursor; The asphalt used can be medium-temperature or high-temperature asphalt of different grades, and can be crushed into powder.

[0021] S7, Oxidation modification: The carbon precursor is blown with hot air at 150~350℃ for 1~3h to obtain an oxidized carbon precursor; during the oxidation process, oxygen-containing functional groups are introduced to cross-link with the asphalt molecules, inhibiting the formation of the molten intermediate phase during the carbonization process, reducing the long-range order of the material, and making the structure more disordered. Since an amorphous carbon structure is formed on the surface of the carbon material, it helps to close the macropores or mesopores to reduce the specific surface area, thereby improving the first charge and discharge coulomb efficiency and reversible capacity.

[0022] S8, high temperature carbonization: subjecting the oxidatively modified carbon precursor to high temperature carbonization treatment to form a hard carbon negative electrode material for a sodium ion battery; Specifically, the oxidized carbon precursor is placed in a high-temperature carbonization furnace, an inert gas is introduced, the air in the furnace is driven out by controlling the flow rate, and the inert gas is maintained, and the temperature is raised from room temperature at a rate of 1-10°C / min to a specified carbonization temperature of 1100-1500°C, and carbonization is maintained at this temperature for 4-16 hours to form a hard carbon negative electrode material for a sodium ion battery. It is particularly emphasized that the furnace must be filled with inert gas and air cannot leak in, otherwise the carbon material will be oxidized into carbon dioxide and the specific surface area of ​​the material will be increased. The carbonization time must also be kept long enough to facilitate the formation of a structure for inserting sodium ions. After carbonization is completed, heating is stopped and the inert gas must be maintained until the material is cooled to below 200°C and removed.

[0023] S9. Dispersing: Use a dispersing machine to disperse the high-temperature carbonized materials into powder.

[0024] S10, sieving: the powdered material is sieved with a 200-500 mesh ultrasonic vibration screen to obtain the final product of the hard carbon negative electrode material for sodium ion batteries. The material on the sieve is returned to the sieving process for further processing.

[0025] In summary, the present invention aims to solve the problem that the existing biomass hard carbon negative electrode materials have large specific surface area and high irreversible capacity, and proposes a method for preparing a biomass hard carbon negative electrode material with low specific surface area. For hard carbon negative electrode materials, the internal microcrystalline structure has more pores and high disorder, and the capacity and voltage curves show the coexistence of slope area and platform area. In particular, the closed pore structure in hard carbon plays a key role in the sodium storage capacity. Therefore, according to the design needs, the adjustable pore structure and active sites at the molecular level are accurately constructed, so that the obtained hard carbon material has good performance consistency, and the performance of rate, capacity and cycle is also good.

[0026] Moreover, as the negative electrode material of sodium ion battery, the specific surface area of ​​carbon material must be reduced to reduce the irreversible capacity of the first charge and discharge and improve the coulombic efficiency and reversible capacity. In general, the specific surface area should be less than 3m 2 / g.

[0027] The present invention specifically uses medium-temperature asphalt or high-temperature asphalt to close the open pores in the carbon material to reduce its specific surface area, thereby improving the sodium storage capacity, and after the macropores or mesopores on the surface are coated with asphalt, a hard carbon structure is formed through a high-temperature carbonization process. In addition, the asphalt raw materials used have the advantages of low cost, easy acquisition, and high carbon product yield. The hard carbon negative electrode material is prepared from biomass raw materials. The sources of biomass raw materials are diverse and the cost is relatively appropriate. Its own unique microstructure reduces the process difficulty of the production process.

[0028] It should be explained in detail that after the surface of the biomass carbon material is coated with asphalt and directly sent to the carbonization furnace, the amorphous carbon obtained after the asphalt carbonization is soft carbon, which will cause the specific capacity of the final material to decrease and the rate charge and discharge performance to decrease. Therefore, it is necessary to perform low-temperature pre-oxidation modification on the asphalt so that oxygen-containing functional groups are introduced into the structure after the asphalt is oxidized, reduce the long-range order of the amorphous carbon in the coating layer, and obtain a pure hard carbon negative electrode material that is basically free of soft carbon.

[0029] Embodiment 1 The biomass raw material used in this embodiment is almond shell. The almond shell is pretreated by washing, drying and other steps to obtain a carbon precursor. The carbon precursor is put into a vacuum heating furnace for heating, the vacuum degree is maintained below 0.08MPa, the heating rate is 5℃ / min, and the temperature is heated to 400℃, and the carbonization time is maintained at this temperature for 3h. After stopping the heating, the vacuum in the heating furnace is maintained until the temperature drops below 100℃, the material is taken out and cooled to room temperature, crushed with a roller mill, and then the crushed material is sieved with a 20-mesh screen. A mixed acid solution containing 5% sulfuric acid, 0.5% hydrofluoric acid, and 1.5% hydrochloric acid (mass percentage) is prepared, and the low-temperature carbonized material after crushing and screening is acid-washed, and the filtered filter cake is washed with water, filtered, and dried. The dried material is finely ground with a mechanical mill with a grading device, and then fully mixed with medium-temperature asphalt powder at a ratio of 100:10, and then put into a fusion machine for fusion to obtain a carbon precursor, and then oxidized with hot air at about 300℃, and taken out for standby. The oxidized carbon precursor is placed in a high-temperature carbonization furnace, and nitrogen is introduced to drive out the air in the furnace. The temperature is raised from room temperature at a rate of 5°C / min to 1300°C. The temperature is maintained for 10 hours, and the heating is stopped while nitrogen is introduced to reduce the furnace temperature to below 200°C. The material is taken out and broken up into powder with a plowshare disintegrator. It is then sieved with a 350-mesh ultrasonic vibrating screen to obtain a hard carbon negative electrode material with a low specific surface area. The sieved large particles are put back into the disintegrator for dissociation. The prepared hard carbon negative electrode material has a D50 of 6~8μm and a specific surface area of ​​1.8~2.4m 2 / g.

[0030] Embodiment 2 The biomass raw material used in this embodiment is coconut shell, which is pretreated by washing, drying and other steps to obtain a carbon precursor. The carbon precursor is put into a heating furnace, and nitrogen is introduced after vacuuming. It is heated under nitrogen protection, and the heating rate is 8°C / min. It is heated to a temperature of 500°C, and the carbonization time is maintained at this temperature for 4 hours. After stopping the heating, wait for the furnace temperature to drop below 100°C, take out the material, cool it to room temperature, and crush it with a roller mill. The crushed material is sieved with a 40-mesh screen. A mixed acid solution containing 10% sulfuric acid, 0.1% hydrofluoric acid, and 2% hydrochloric acid (weight percentage) is prepared, and the low-temperature carbide after crushing and screening is acid-washed, and the filtered filter cake is washed with water, filtered, and dried. The dried material is finely ground with a jet mill with a grading device, and then fully mixed with powdered high-temperature asphalt at a ratio of 100:6, and then put into a fusion machine for fusion to obtain a carbon precursor, and then oxidized with hot air at about 270°C for 3h, and taken out for standby. The oxidized carbon precursor is placed in a high-temperature carbonization furnace, and nitrogen is introduced to drive out the air in the furnace. The temperature is raised from room temperature at a rate of 7°C / min to 1400°C. The temperature is maintained for 8 hours, and the heating is stopped. Nitrogen is introduced to reduce the furnace temperature to below 200°C. The material is taken out, and it is broken up and dissociated with a dispersing machine. It is then sieved with a 400-mesh ultrasonic vibrating screen to obtain a hard carbon negative electrode material with a low specific surface area. The sieved large particles are put back into the dispersing machine for dissociation. The prepared hard carbon negative electrode material has a D50 of 5~7μm and a specific surface area of ​​2.0~2.6m 2 / g.

[0031] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.

Claims

1. A method for preparing a low specific surface area biomass hard carbon negative electrode material, characterized in that: It includes the following preparation steps: S1. Pretreatment: pretreating the biomass raw material to obtain a carbon precursor; S2. Low-temperature carbonization: heating the carbon precursor at a temperature of 300-600°C to obtain a low-temperature carbide; S3, crushing: cooling the low-temperature carbide to room temperature and then crushing it; S4, pickling: preparing pickling liquid, and pickling the crushed low-temperature carbide; S5, fine grinding: finely grind the pickled material with a mechanical mill or a jet mill; S6. Fusion: Fusion of the finely ground product with asphalt, where the asphalt fills and coats the macropores or mesopores on the surface of the carbon material to form a carbon precursor; S7, oxidation modification: blowing the carbon precursor with hot air at 150-350° C. for 1-3 hours to obtain an oxidized carbon precursor; S8. High temperature carbonization: The oxidized carbon precursor is subjected to high temperature carbonization treatment at 1100~1500℃ to form a hard carbon negative electrode material for sodium ion batteries.

2. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: The preparation method also includes the following steps: S9. Break up: After high-temperature carbonization, cool the material to below 200°C and take it out. Use mechanical means to break up the agglomerated or compacted material into powder; S10, sieving: the powdered material after being dispersed is passed through a 200-500 mesh ultrasonic vibration screen to obtain the final product of the hard carbon material for the negative electrode of the sodium ion battery. The material on the screen is returned to the dispersing step for further processing.

3. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: The biomass raw materials used are any one or more of nut shells such as almond shells, coconut shells, walnut shells, sisal leaves, crop straw, etc.; The asphalt used is medium-temperature or high-temperature asphalt, which is crushed into micron-sized powder.

4. The method for preparing a low specific surface area biomass hard carbon negative electrode material according to claim 3, characterized in that: The pretreatment methods include cleaning, sun drying and the like.

5. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: In S2, the specific operations of the low-temperature carbonization treatment are: putting the carbon precursor into a vacuum heating furnace or an inert gas heating furnace for heating and carbonization; When a vacuum heating furnace is used, the furnace is evacuated, the vacuum degree is maintained at 0.04~0.08MPa, the heating rate is 3~10℃ / min, the temperature is heated to 300~600℃, and the carbonization time is maintained at this temperature for 2~4h; When an inert gas heating furnace is used for heating carbonization, the heating chamber is first evacuated and then an inert gas is injected. The inert gas can be nitrogen or argon, and is also heated to a temperature of 300~600℃.

6. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: In S3, the specific crushing process includes: taking out the low-temperature carbide from the vacuum heating furnace or the inert gas heating furnace and cooling it to room temperature, crushing it with a double-roll mill, and sieving the crushed material with a 10-50 mesh screen, and returning the screened material to the double-roll mill for re-crushing.

7. The method for preparing a low specific surface area biomass hard carbon negative electrode material according to claim 1, characterized in that: The pickling solution is composed of the following substances in percentage by mass: 1% to 10% sulfuric acid, 0.1% to 1% hydrofluoric acid, and 1% to 2% hydrochloric acid. After pickling, water washing is performed to wash out the acidic substances, and the filter cake obtained by filtration is then dried.

8. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: In S5, the equipment used for fine grinding is a mechanical mill or a jet mill with a classifying device.

9. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: In S6, the equipment used for the fusion treatment is a fusion machine. The finely ground product is fully mixed with asphalt at a mass ratio of 100:(1~15) and then put into the fusion machine for fusion coating to form a carbon precursor.

10. The method for preparing a biomass hard carbon negative electrode material with a low specific surface area according to claim 1, characterized in that: In S8, the carbon precursor oxidized by hot air is placed in a high-temperature carbonization furnace, an inert gas is introduced, the flow rate of the inert gas is controlled, the air in the furnace is driven out, and the inert gas is kept flowing. The temperature is raised from room temperature at a rate of 1-10°C / min to 1100-1500°C, and the temperature is maintained for 4-16 hours for high-temperature carbonization to form a hard carbon material for the negative electrode of a sodium ion battery.

Citation Information

Cited By

  • Preparation method and application of asphalt-based carbon material

    CN120004266A

  • Element-doped biomass hard carbon negative electrode material and preparation method thereof

    CN120622464A

  • Pre-oxidized asphalt synergistically-coated double-layer hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN121565820A

  • Pre-oxidized pitch synergistically coated double-layer hard carbon negative material, preparation method thereof and sodium ion battery

    CN121565820B